Integrating Academic Research Activities in Education into Real Life Problem Solving: The Efficacy and Barriers from Lecturers’ Perspectives - Adeyemi, B.A.; Adeyemi, B.B. (American Journal of Education and Learning, 2019)
The study determined lecturers’ perceived efficacy of academic research activities in education towards solving real-life problems. It determined the extent of synergy between academic research activities in education and its application in solving real-life problems. It also examined the perceived barriers confronting integration of academic research activities in education towards solving real-life problems and finally determined the difference in the lecturers’ perceived efficacy of academic research activities in education towards solving real-life problems. The study employed a survey research design. The sample size consisted of 150 lecturers from five faculties in Obafemi Awolowo University, Ile-Ife, Osun State, Nigeria. An instrument used for the data collected was trial tested and yielded a reliability coefficient of 0.81 using Cronbach Alpha Coefficient. The results among others showed that no significant difference existed in the lecturers’ perceived efficacy of academic research activities in education towards solving real-life problems based on cadres (F= 0.632, p>0.05). The study concluded that the problem of incessant power failure, inadequate funding, corruption and mismanagement be rectified.